51 Evaluation of a Clinical Pharmacy Service on an Inpatient Ward in an Acute Hospital. (16th September 2019) - McGann, Ciara; Love, Bernie; Carr, James; O'Connor, Marie; Dolan, Eamon
Abstract: Background: Intensive clinical pharmacy input from admission to discharge has been shown to improve patient outcomes. The clinical pharmacy service in our institution has historically been under-resourced. The aim of this study is to develop a ward-based clinical pharmacy service and to evaluate its impact using a number of clinical, safety and financial metrics. Methods: A clinical pharmacist was assigned to provide pharmaceutical care to patients on a Medicine for the Older Person ward. Over an eight week period, the pharmacist prospectively recorded her interventions/activities. To assess impact on patient care, interventions were graded according to the Eadon criteria. The potential cost avoidance associated with interventions was estimated. Medication incident reporting was analysed to assess the impact on patient safety. Results: 87% of patients had at least one pharmacist intervention, across a spectrum of activities including medication reconciliation and clinical review. 90% of interventions requiring follow-up with the medical team were accepted and resulted in a change to patient's care. Eadon grading of interventions deemed 99% to be significant, with 81% improving the standard of patient care. Two different methods were used to estimate potential cost avoidance: one estimated annual savings of €154, 103 - €344, 926; the other estimated these at €174, 373. Given current pharmacist salary costs, this equates to a cost-benefit ratio of 2.8:1 to 6.3:1. (This does not include the 27% reduction in drug spend observed during the study period. However, more longitudinal data are required to confirm and characterise this phenomenon.) A five-fold increase in medication incident reporting from the ward was observed, suggestive of an enhanced culture of patient safety. Conclusion: This study assessed and quantified a wide spectrum of pharmacist contributions to medication management and safety. Costing of these contributions estimates the cost-benefit ratio of the clinical pharmacy service, providing compelling support for the extension of this service throughout the hospital.